Process Integration and Circular Economy for Renewable and Sustainable Energy Systems. (December 2019) - Klemeš, Jiří Jaromír; Varbanov, Petar Sabev; Walmsley, Timothy Gordon; Foley, Aoife
Abstract: The mission of Renewable and Sustainable Energy Reviews (RSER) is to communicate the most significant and relevant critical thinking in renewable and sustainable energy research and development, bringing together the research community, the private sector and policy and decision-makers. The aim of the journal is to share problems, solutions, novel ideas and technologies that support the transition to a low-carbon future and achieve the global emissions targets as established by the United Nations Framework Convention on Climate Change (UNFCC). The Process Integration, Modelling and Optimisation for Energy Saving and Pollution Reduction (PRES) 2018 conference brought together the following topics through interdisciplinary dialogue: (a) Process Integration for sustainable development; (b) Process analysis, modelling and optimisation; (c) Total Site Integration; (d) Heat transfer and heat exchangers; (e) Energy-saving and clean technologies; (f) Sustainable processing and production; (g) Renewable and high efficiency utility systems; (h) Footprint minimisation and mitigation; (i) Operations and supply chain management; (j) Waste minimisation, processing and management; (k) Batch process analysis and integration; (l) Process network dynamics, flexibility and control; (m) Industrial implementation and optimisation; (n) Numerical fluid flow and heat transfer simulation; (o) Sustainability and Process Integration teaching, learning and knowledge tools. This Virtual Special Issue (VSI) captures many of the most significant developments in renewable and sustainable energy research.